2019
DOI: 10.1016/j.ijcard.2018.06.106
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy modulates thickness and inflammatory profile of human epicardial adipose tissue

Abstract: Background: Epicardial adipose tissue (EAT) thickness and pro-inflammatory status has been shown to be associated with several cardiac diseases, including aortic stenosis (AS). Thus, cardiac visceral fat could represent a potential new target for drugs. In the present study we evaluate the effect of statin therapy on EAT accumulation and inflammation. Methods: Echocardiographic EAT thickness was assessed in 193 AS patients taking (n.87) and not taking (n.106) statins, undergoing cardiac surgery. To explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 29 publications
4
58
0
2
Order By: Relevance
“…Since the increasing evidence on the role of cardiac visceral adiposity in the pathophysiology of cardiovascular diseases, the measurement of EAT thickness should be strongly encouraged. In this regard, we have recently observed that EAT measurement proposed in this study is directly correlated with the levels of inflammatory mediators secreted by EAT [14]. Given its proximity to the myocardium and absence of fascial boundaries, EAT directly influences myocardial homeostasis through vasocrine and paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Since the increasing evidence on the role of cardiac visceral adiposity in the pathophysiology of cardiovascular diseases, the measurement of EAT thickness should be strongly encouraged. In this regard, we have recently observed that EAT measurement proposed in this study is directly correlated with the levels of inflammatory mediators secreted by EAT [14]. Given its proximity to the myocardium and absence of fascial boundaries, EAT directly influences myocardial homeostasis through vasocrine and paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 64%
“…At this level, it is possible to directly visualize and measure the fat deposit between the visceral layer of the pericardium and the myocardium. In patients with aortic stenosis, we have recently reported [14] that this measure is accurate and reproducible. In the same population, we have also demonstrated that the increase of EAT thickness directly correlates with the levels of EAT-derived inflammatory mediators, thus being expression of an EAT proinflammatory phenotype.…”
Section: Introductionmentioning
confidence: 98%
“…Nakazato et al [72] showed a 2% regression in EAT volume in 54 patients who lost 5% of their initial body weight in 4 y, compared to a 23% increase in 71 subjects who gained weight. Two groups of investigations reported that EAT volume decreased after intensive lipid-lowering therapy with statins [73,74]. The latter may have occurred because of the known anti-inflammatory activity and inhibition of vasa-vasorum proliferation by statins, which are believed to directly contribute to the development of atherosclerosis [75].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Statins are commonly used in patients with obesity and type 2 diabetes to prevent atherosclerotic events, but they have striking effects in lessening epicardial adipocyte mass and inflammation, [98][99][100][101] and thereby preventing fibrosis in the underlying myocardium. 102,103 This anti-inflammatory action may explain why statins ameliorate the development of an atrial myopathy in experimentally induced cardiac stress and in patients with AF.…”
Section: Statinsmentioning
confidence: 99%